POLEX-SOUTH DATA, PART 2 : MICROMETEOROLOGICAL DATA AT MIZUHO STATION, ANTARCTICA IN 1979 - WADA, Makoto; YAMANOUCHI, Takashi; MAE, Shinji; KAWAGUCHI, Sadao (National Institute of Polar Research, 1981)
P(論文) departmental bulletin paper